Answer:
Quotient property of exponents:
Substitute - such that:
Step-by-step explanation:
The correct answer is:
6.6 years.
Explanation:
Since he goes from making $28,000 per year to $14,000 per year, he will lose $14,000 each year that he works part-time. He intends to do this for 2 years; this will be a loss of $14000(2) = $28,000.
We will add the cost of his degree to this: 28,000+5,000 = $33,000.
He will be making $33,000 per year when he graduates. This is 33000-28000 = 5000 more per year than he made before.
To find out how many years it will take him to recover his investment, we divide the amount he loses, 33,000, by the extra amount he will make per year, 5000:
33000/5000 = 6.6
Answer: C 6.6 years
Step-by-step explanation: edge 2022
(dont write random answers pls!)
Answer:
to find the answer, you need to find the measure of the angle on the other side of the 142. and since it's a straight line, those two angles measures are =to 180 (they're supplementary angles). so the measure of that angle is 38 degrees. to find the measure of the remaining angle, you subtract the angle measures you already know from 180 (because the sum of interior angles in a triangle is 180.) to, the answer is:
180-90-38= 52 degrees or A
(–4 + i) + 4i = –4 + (i + 4i) is the associative property of addition. Thus, option A is correct.
According to the associative property of additionally, whenever at least three figures are added together, the outcome is unaffected by the sequence in which the individual numbers are added.
In the first given condition is is stated:
(–4 + i) + 4i = –4 + (i + 4i)
-4 + i + 4i = -4 + i + 4i
5i - 4 = 5i - 4
As the LHS = RHS, the property is said to be valid for the associative property of addition.
Therefore, option A is the correct option.
Learn more about associative property of addition, here:
#SPJ7
Which equation shows an example of the associative property of addition?
(–4 + i) + 4i = –4 + (i + 4i)
(–4 + i) + 4i = 4i + (–4i + i)
4i × (–4i + i) = (4i – 4i) + (4i × i)
(–4i + i) + 0 = (–4i + i)
A. (–4 + i) + 4i = –4 + (i + 4i)
Step-by-step explanation:
edge2020
Have a great day y'all :)
y-x=5
a)(-10,-5)
b)(-7,-2)
c)(7,2)
d)(5,10)
Answer:
x = 5
Step-by-step explanation:
Because the red-marked lines are parallel, we know that the ratios are the same
5x : 45 = 20 : 36
5x/45 = 20/36
5x * 36 = 20 * 45
5x * 4 = 20 * 5
5x * 1 = 5 * 5
x = 5
2(2x+6)
Answer:
x = 3
Step-by-step explanation:
2(2x + 6)
4x + 12
4/4 = 1
12/4 = 3
x = 3
Hopefully this helps you :)
pls mark brainlest ;)